Exhaustion of Racing Sperm in Nature‐Mimicking Microfluidic Channels During Sorting. Issue 20 (16th May 2013) - Tasoglu, Savas; Safaee, Hooman; Zhang, Xiaohui; Kingsley, James L.; Catalano, Paolo N.; Gurkan, Umut Atakan; Nureddin, Aida; Kayaalp, Emre; Anchan, Raymond M.; Maas, Richard L.; Tüzel, Erkan; Demirci, Utkan
<x xml:space="preserve">Abstract</x> Fertilization is central to the survival and propagation of a species, however, the precise mechanisms that regulate the sperm's journey to the egg are not well understood. In nature, the sperm has to swim through the cervical mucus, akin to a microfluidic channel. Inspired by this, a simple, cost‐effective microfluidic channel is designed on the same scale. The experimental results are supported by a computational model incorporating the exhaustion time of sperm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>